A case study of cooperative purchasing programs in transportation organisations. Issue 3 (2015) - Beruvides, Mario G.; Simonton, James L.; Waters, Natalie M.; Palikhe, Himlona; Chaivichitmalakul, Siva
Vast numbers of public transit agencies have increased demands for purchasing and maintenance. Transit agencies organisational growth has increased significantly based on vehicle maintenance costs that include vehicle parts, equipment, and services. Cooperative purchasing programs are methodologies used to share or bundle purchasing volumes, information, and resources. Cooperative purchasing programs can save public transit agencies time and money because of the economies of scale from increased purchased quantities. This paper identifies current preferences needed when considering utilising cooperative purchasing programs through customised questionnaires. Several Texas transportation organisations were featured in this study. These questionnaires highlight the differences between agencies participating in cooperative purchasing programs and agencies not participating in cooperative purchasing programs along with their programmatic paradigms and their current practices regardless of public transit agency type. The results of the questionnaires show the different agencies' purchasing patterns. Vehicles, vehicle maintenance and vehicle insurance are the three of the top four purchasing items for public transit agencies surveyed in this study both utilising and not utilising cooperative purchasing programs. This paper also provides suggestions on best practices for cooperative purchasing programs.